Refractory lymphedema of the hand: an unusual presentation of recurrent herpes simplex virus infection - Ali Majdzadeh; Mohammed I. AlJasser; Sunil Kalia (Our Dermatology Online, 2016)
Introduction: Herpes Simplex Virus (HSV) infection of the hand resulting in lymphatic complications such as lymphangitis and lymphedema is exceedingly uncommon. Although these complications typically resolve in 21 days, they can be persistent and may not resolve even with antiviral use, thereby mimicking dyshidrotic eczema or a bacterial event and often being misdiagnosed and inappropriately treated as such. We report a case of frequently recurring HSV infection of the hand over a long period of time resulting in refractory lymphedema which did not resolve with antiviral treatment. We further endeavor to raise awareness about this highly unusual presentation of HSV infection. A comprehensive review of the literature was conducted for similar cases using PubMed and Medline. Case Report: This is the first reported case with nearly a decade-long interval between the onset of primary HSV infection and the development of chronic lymphedema. Although valacyclovir significantly reduced the episodic aggravation of the lymphedema, it did not entirely resolve it. Similar cases of persistent lymphedema also included a long history of untreated and recurrent HSV infection of the hand, suggesting that this lymphatic outcome may be circumvented by prompt treatment with antivirals. Conclusion: This case report not only presents a highly uncommon lymphatic manifestation and unusual timeline of exacerbation of the very common HSV infection, but also highlights the importance and benefits of early initiation of antiviral therapy and the prevention of reactivation.